The Horizontal and Vertical Distribution of Deep-Sea Sediments Fungal Community in the South China Sea - Feng, Li; Song, Qianqian; Jiang, Qun; Li, Zhiyong (Frontiers in Marine Science, 2021)
Although diverse fungi have been found in the deep-sea habitats, the space distribution of fungi has not been well characterized. In this study, the fungal horizontal and vertical distribution of the deep-sea sediments, four locations, three depths each, in the South China Sea, were compared using ITS2 high-throughput sequencing. It was revealed that the South China Sea deep-sea sediments harbor diverse marine fungi, including 82.39% Ascomycota, 8.10% Basidomycota, 0.55% Zygomycota and 8.96% unknown fungi. The results indicate that fungal community structure is not uniform among the different sediment habitats, in particular, the fungal abundance and diversity increase with the depth of the sediments from 0 to 2 m. Though surface sediments have similar fungal diversity across the 4 locations, 1 m and 2 m deep sediments show obvious location-dependent fungal community structure. This is the first time to compare the horizontal and vertical distribution of fungal community among different deep-sea sediments in the South China Sea by high-throughput sequencing, providing novel insights into the space distribution characteristics of deep-sea sediments fungi.